2013
DOI: 10.1179/1743294412y.0000000093
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of electroless Ni–P–TiO2 nanocomposite coatings using Taguchi

Abstract: This paper reports an experimental study of corrosion characteristics of electroless Ni-P-TiO 2 nanocomposite coatings. Coating process parameters are optimised for maximum corrosion resistance based on L 9 Taguchi orthogonal design with four process parameters, namely, concentration of nickel source solution, concentration of reducing agent, concentration of TiO 2 powder and bath temperature. Corrosion behaviour of the electroless Ni-P-TiO 2 nanocomposite coatings was evaluated in 3?5 wt-%NaCl aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It was observed from the investigations made by Hosseini et.al and Rajesh et al 13 , 29 that the corrosion rate of pure copper and copper coated with TiO 2 were higher compared to Cu/Al 2 O 3 composites. Ajeel et al 30 confirmed that the reinforced copper alloy with 3 wt.% of Al 2 O 3 and TiO 2 has a lower corrosion rate than reinforced copper alloy reinforced with 1.5 wt.% of Al 2 O 3 and TiO 2 .While the reinforced alloys with 1.5 wt.% of Al 2 O 3 and TiO 2 has lower corrosion rate compared to the copper alloy. Raghav et al 31 studied the corrosion of copper –TiO 2 nanocomposite coatings on steel.…”
Section: Introductionmentioning
confidence: 97%
“…It was observed from the investigations made by Hosseini et.al and Rajesh et al 13 , 29 that the corrosion rate of pure copper and copper coated with TiO 2 were higher compared to Cu/Al 2 O 3 composites. Ajeel et al 30 confirmed that the reinforced copper alloy with 3 wt.% of Al 2 O 3 and TiO 2 has a lower corrosion rate than reinforced copper alloy reinforced with 1.5 wt.% of Al 2 O 3 and TiO 2 .While the reinforced alloys with 1.5 wt.% of Al 2 O 3 and TiO 2 has lower corrosion rate compared to the copper alloy. Raghav et al 31 studied the corrosion of copper –TiO 2 nanocomposite coatings on steel.…”
Section: Introductionmentioning
confidence: 97%
“…presents the amorphous structure of the Ni-P alloy, which was analyzed by XRD. Only one broad peak around 2θ = 45°was observed, indicating the complete amorphous character of the Ni-P alloy [26][27][28][29], as shown in figures 1(a)-(c). With an increase in the heating temperature, both the number and the strength of the Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of solid particles into the matrix could remarkably improve the mechanical and physiochemical properties of composite coatings. For example, hard particles such as Al 2 O 3 [4,5], SiC [6,7], SiO 2 [8], TiO 2 [9], and diamond [10] enhance the hardness and wear resistance of composite coatings. Solid lubricant particles such as MoS 2 [11,12], PTFE [13], and BN(h) [14] lower the frictional coefficient of composite coatings and consequently reduces wear loss.…”
Section: Introductionmentioning
confidence: 99%